Performance of Ashgourd genotype under Hyderabad conditions of Andhra Pradesh (Indian Journal of Arid Horticulture, 2025)
Ashgourd [Benincasa hispida (Thumb) Cogn.] is an important warm vegetable grown for its fruit used in con- fectionery and ayurvedic medicinal preparations (Indira and Peter, 1987). Among the cucurbitaceous vegetable, where as ripe fruit is boiled in sugar to make a confectionery known as petha (Joydip Mandal et. al. 2002).
Keywords: confectionery; cucurbitaceous; nondescript; yielding